A molecular absorption line survey towards the AGN of Hydra-A. Issue 1 (28th May 2020) - Rose, Tom; Edge, A C; Combes, F; Hamer, S; McNamara, B R; Russell, H; Gaspari, M; Salomé, P; Sarazin, C; Tremblay, G R; Baum, S A; Bremer, M N; et al.
ABSTRACT: We present Atacama Large Millimetre/submillimetre Array observations of the brightest cluster galaxy Hydra-A, a nearby ( z = 0.054) giant elliptical galaxy with powerful and extended radio jets. The observations reveal CO(1−0), CO(2–1), 13 CO(2–1), CN(2–1), SiO(5–4), HCO + (1–0), HCO + (2–1), HCN(1–0), HCN(2–1), HNC(1–0), and H2 CO(3–2) absorption lines against the galaxy's bright and compact active galactic nucleus. These absorption features are due to at least 12 individual molecular clouds that lie close to the centre of the galaxy and have velocities of approximately −50 to +10 km s −1 relative to its recession velocity, where positive values correspond to inward motion. The absorption profiles are evidence of a clumpy interstellar medium within brightest cluster galaxies composed of clouds with similar column densities, velocity dispersions, and excitation temperatures to those found at radii of several kpc in the Milky Way. We also show potential variation in a ∼10 km s −1 wide section of the absorption profile over a 2 yr time-scale, most likely caused by relativistic motions in the hot spots of the continuum source that change the background illumination of the absorbing clouds.